Enostosis (osteopoikylosis, bone islands) in medieval (14- 15th centuries) skeletons - Józsa, László; Farkas, Gyula L. (Acta Biologica Szegediensis, 2008)
Enostosis (i.e. osteopoikylosis, bone islands, etc.) is a focus of mature cortical bone within cancellous bone. Bone islands are often recognized on radiographic pictures taken for other diagnostical purpose. The authors examined x-ray images of 652 long bones and 44 innominate bones of 124 adult skeletons from the 14-15th centuries AD. Six cases of enostoses were recognized (2 innominate bones, 2 fibulas, 1 femur head and 1 tibia). The biggest alteration was 22x9 mm, while most of the bone islands were 2-5 mm in size. Histological examination was performed in two cases. Microscopical view of one case showed lamellar (cortical) bone; in the other case woven bone structure was found. Enostosis of archeological bones can only be diagnosed performing routine radiographic examination.